Directive Speech Acts in the Speech of Tuan Guru: A Pragmatic Analysis - Haq, M. Mizanul; Nasri, Ulyan; Hafiz, Hairori Sahrul (LPPM Universitas Bumigora Mataram, 2025)
Language serves as a crucial tool in delivering messages, shaping interactions, and influencing audiences, particularly in public speeches. One essential linguistic feature commonly used by speakers is directive speech acts, which function to instruct, request, advise, or encourage listeners to perform certain actions. This study analyzes directive speech acts in the speech of TGH. M. Hilmi Nadjmuddin, a prominent Islamic leader whose sermons contain strong educational and leadership values. The objectives of the study are to identify and classify directive speech acts, examine their pragmatic functions, and explore the embedded values of leadership and education. This study uses a qualitative descriptive method with a pragmatic approach; the data were drawn from selected transcripts of his speeches, categorized by directive type, and analyzed contextually. The findings reveal various directive speech acts, such as commands, requests, advice, and suggestions, each serving different communicative purposes. The analysis further shows that these directive strategies not only fulfill communicative intentions but also reflect discipline, moral guidance, and leadership within the pesantren tradition. These findings highlight the significance of directive speech acts as instruments for shaping character, influencing audiences, and promoting educational values, while contributing to pragmatic studies in religious discourse.